RMySQL for the analysis of data of postulants and entrants of the biomedical area to the National University of the Altiplano (Puno, Perú) - Jiménez Chura, Adolfo Carlos (2017)
The objective was to apply RMySQL, dplyr and graphing functions of the database to the processes of admission at the Central Admission Commission at the National University of the Altiplano. The source code of the functions that return data.frames of the observations of the database and functions was implemented to generate the graphs of dynamic form such as ggplot and barplot; summarise, select, group_by, merge, arrange, unique and others of project R were used. The result indicates that the percentage of entrants, of the ordinary and extraordinary admission processes, according to the number of applicants is: 22.91% were admitted to Medicine, Veterinary and Animal Science; 10.87% to Nursing; 26.83% a Biology; 2.44% in Human Medicine; 17.64% to Human Nutrition and 7.25% to Dentistry, included between March 17, 2013 and January 22, 2017; also, the percentage of admissions by origin of school in the urban and rural area obtained shows that the Professional School of Biology has the highest percentage, 27.52% and 19.48% of the urban and rural area; Medicine, Veterinary and Animal Husbandry 22.87% and 15.53% of the urban and rural area; Human Nutrition 18.48% and 8.09% of the urban and rural area; Nursing 11.45% and 5.62% of the urban and rural area; Dentistry 7.51% and 3.24% of the urban and rural area; and Human Medicine 2.49% and 2.09% urban and rural area.